Marikana : taking a subaltern sphere of politics seriously - Naicker, Camalita (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
This thesis aims to open up the realm of what counts as political in the context of the Marikana strikes and subsequent massacre. It does primarily by taking into account the social, political and cultural context of Mpondo workers on the mines. Many narrow Marxist and liberal frameworks have circumscribed the conception of the 'modern' and the 'political' so much so that political organisation which falls outside of this conceptualisation is often regarded as 'backward' or 'archaic'. It will provide an examination of the history, culture and custom of men, who have, for almost a hundred years migrated back and forth between South African mines and Mpondoland. This not only reveals differing modes of organising and engaging in political action, but also that the praxis of democracy takes many forms, some of which are different and opposed to what counts as democratic in Western liberal democracy. By considering what I argue, following some of the insights from the Subaltern Studies collective in India, to be a subaltern sphere of politics and history, it is possible to better understand the way workers organised and acted. The thesis also argues that most labour and nationalist historiography has been silent on the political contributions of women because of how Marxist/liberal analysis frames struggles through disciplined notions of work and resistance. Rather than objectifying workers as representatives of a homogenous and universal class of people devoid of context, the thesis has linked 'the worker' to the community from which s/he comes and community specific struggles, which are supported and sustained, often, by the parallel struggles of women in the community.
Keywords: Miners -- South Africa -- Rustenburg -- Social conditions -- 21st century; Mineral industries -- Political aspects -- South Africa; Violence -- South Africa -- Rustenburg; Massacres -- South Africa -- Rustenburg; Strikes and lockouts -- Miners -- South Africa; Political leadership -- South Africa; Industrial relations -- South Africa; Marxist criticism; Marikana (Rustenburg, -- South Africa)